What Is Philosophy? - Munro, Michael (Book collections on Project MUSE., 2020)
It's clear that "philosophy" comes from the Greek "philosophia," love of wisdom. What is not at all clear is what that phrase means. In the connection it articulates between love and wisdom, what, precisely, does philosophy name?This small book, or extended essay, is divided into three sections. The first section (What is Philosophy?) takes seriously Gilles Deleuze and Felix Guattari's contention in their book of the same title that, "The nonphilosophical is perhaps closer to the heart of philosophy than philosophy itself, and this means that philosophy cannot be content to be understood only philosophically or conceptually, but is essentially addressed to nonphilosophers as well?" (including the nonphilosopher in every philosopher). The second section (On Argument) interrogates the status and value of evidence, and self-evidence. The third section (On Not Knowing) generalizes a parenthetical observation of Agamben's on Heidegger, "If we may attempt to identify something like the characteristic Stimmung of every thinker, perhaps it is precisely this being delivered over to something that refuses itself that defines the specific emotional tonality of Heidegger's thought": Might not philosophy be defined, the phil of sophia, precisely, as what it is to be delivered over to something that refuses itself? That is precisely what this small explores.